2002
DOI: 10.1063/1.1490622
|View full text |Cite
|
Sign up to set email alerts
|

Conduction processes in conjugated, highly regio-regular, high molecular mass, poly(3-hexylthiophene) thin-film transistors

Abstract: Highly regio-regular poly(3-hexylthiophenes) (P3HT) thin films have been produced using the Tzrnadel method. They have head to tail counts approaching very close to 100% and high molecular mass. Thin-film transistors and Schottky diodes have been used to study the effects of counter ion and carrier density on field-effect and bulk mobility, respectively. The density of counter ions was increased using 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) and had a profound effect on both the field effect and bulk mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…4B, calculated using the standard method). Both of these values are comparable to those obtained from bulk organic FETs based on metal electrodes, [52][53][54][55] strongly suggesting that cut 2D planar graphene sheets can function as efficient electrodes, realizing the functions of macroscopic metal electrodes at the nanometer scale. We found that the threshold voltage (V T ) in these devices is approximately þ95 V, a significant positive shift.…”
Section: Resultssupporting
confidence: 67%
“…4B, calculated using the standard method). Both of these values are comparable to those obtained from bulk organic FETs based on metal electrodes, [52][53][54][55] strongly suggesting that cut 2D planar graphene sheets can function as efficient electrodes, realizing the functions of macroscopic metal electrodes at the nanometer scale. We found that the threshold voltage (V T ) in these devices is approximately þ95 V, a significant positive shift.…”
Section: Resultssupporting
confidence: 67%
“…Polyalkylthiophenes have been found to be an interesting class of conductive polymers because of their good solubility, high chemical stability, and high charge-carrier mobility. [25][26][27] Padinger et al first reported that thermal annealing of the P3HT:PCBM blend resulted in an improvement in solarcell properties. [8] Yang et al found that thermal annealing induces an enhanced crystallization of P3HT, explaining the improvement in solar-cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…High-mobility polymer TFTs (mobility of 0.01-0.1 cm 2 /(V s)) have been made with poly(9,9′-dioctylfluorene-co-bithiophene) (F8T2), 9,10 poly[5,5′-bis(3-dodecyl-2-thienyl)-2,2′-bithiophene] (PQT), 11,12 and regioregular poly(3-hexylthiophene) (P3HT). [13][14][15][16][17] The charge carrier mobility of P3HT has been related to the regioregularity, 18 numberaverage molecular weight (MW), 19,20 casting solvent, 13,21 and carrier concentration. 22 The properties of polyfluorene films also depend on MW.…”
Section: Introductionmentioning
confidence: 99%